The perceptions of parents and teachers about the learning and teaching of Setswana as a first language in High Schools - Mofokeng, Sharlotte Thato (University of Limpopo (Turfloop Campus), 2013)
This research looks at the perceptions of parents and teachers about the learning and teaching of Setswana. It looks at Setswana not only as a subject but also as a first language that learners speak at home. It is said that learners have a negative attitude about learning their mother tongue, so this study aims at looking whether parents and teachers are indeed aware of this attitude o if there is an attitude at all. It also intend to indicate whether parents and teacher have a way of discouraging these learners about learning their mother tongues. Since English is seen as the most prestigious language parents may feel that their learners have to be competent in English or they will not achieve much or anything. As teachers teach the language that learners do not appreciate, how do they deal with discouraged learners? Most of all it plans to demonstrate and/or advice learners, parents and teachers about the importance of learning mother tongue in school especially now that they are in high school where by they are capable of making decision about what future path do they want to take. The research tools that are used are questionnaires and interviews. There is a selected number of parents and teachers that will participate. The teachers will answer questionnaires while parents will be interviewed. The data will be analyzed textually also with the help of the SPSS software. The data will be analyzed and interpreted as what they mean for the research and how they have helped that study as a whole and also how they can help further studies if there are any. This study aims to reach the department of education so that maybe they can be able to revise the curriculum of Setswana or maybe change the content. Most importantly it intends to show learners that mother tongue is not a dead end as they make it out to be. They may be as successful with language as they can be with other professions.
Thesis (M.A. (Translation and Linguistics Studies)) -- University of Limpopo, 2013
Keywords: Teaching; Perception; Learning; Teaching and learning; Tswana language -- Study and teaching (Secondary)